A novel face-centered-cubic high-entropy alloy strengthened by nanoscale precipitates. (November 2019) - Qin, Gang; Chen, Ruirun; Liaw, Peter K.; Gao, Yanfei; Li, Xiaoqing; Zheng, Huiting; Wang, Liang; Su, Yanqing; Guo, Jingjie; Fu, Hengzhi
Abstract: A new single-phase face-centered-cubic (FCC) Co9 Cr7 Cu36 Mn25 Ni23 [atomic percent, similar hereinafter] high-entropy alloy (HEA) was prepared by arc melting. A uniform distribution of nanometer-sized precipitates was achieved. The tensile yield strength, ultimate tensile strength, and elongation were 401 MPa, 700 MPa, and 36%, respectively. The energy-dispersive spectrometer results showed that the nano-precipitates were rich in Co and Cr elements. Moreover, the crystal-forming behavior and the nanoscale-precipitates-forming mechanism were revealed. Graphical abstract: The nano-precipitates phase forming process.Unlabelled Image